THE EFFECT OF ROUNDTABLE STRATEGY ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Meida Rabia Sihite; Linda Astuti Rangkuti; Kartina Sitepu (FKIP Universitas Al Washliyah Medan, 2022)
The objective of this study is to find out whether Roundtable Strategy significantly affects students’ achievement in writing descriptive text. It was conducted by using experimental research design. The population of this research was the tenth grade students of SMK Dwi Tunggal Tanjung Morawa which consisted of two parallel classes with the total number of students was 70. By applying cluster random sampling technique, class X TKJ-2 consisting of 35 students was selected as the experimental group and class X TKJ-1 consisting of 35 students was selected as the control group. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. It was found the value of t-observed was 3.15 with the degree of freedom (df)=58 at the level of significance α=0.05. It meant that t-observed value was higher than t-table value (3.15>2.00). In conclusion, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was succesfully rejected. Thus, Roundtable Strategy significantly affects students’ achievement in writing descriptive text.